The sleep prescription : seven days to unlocking your best rest - Prather, Aric (Penguin Books, an imprint of Penguin Random House LLC, 2022)
"From renowned sleep scientist Dr. Aric Prather, a book that offers a simple yet powerful plan to improve your sleep in seven days We need to sleep to survive. If we stopped sleeping, we would die. Sure, it would take a while, but sleep is as essential as food, water, and oxygen. Eventually, without it, our bodies begin to shut down. So why on earth can something that should be so natural, instinctual, and automatic be so hard? Dr. Aric Prather studies sleep for a living, and he'll tell you right off the bat that there's usually one major thing that gets in the way of sleep: you. Not just you. All of us. We are great at getting in the way of our own sleep. We don't mean to. And we're not making obviously bad choices. In the sleep clinic at the University of California, San Francisco, Dr. Prather has a line out the door of people struggling to achieve good sleep. By the time they come to him, they've tried everything. In The Sleep Prescription, Dr. Prather shares the most powerful solutions that he uses to help his patients at the clinic achieve restorative sleep. Going beyond the obvious solutions, Dr. Prather shares surprisingly simple yet deeply effective techniques that will help you lie back and let sleep work its magic. Over the course of seven days, this book will teach you how to get out of your own way, so that your body can do what it was built to do: sleep"--